The Analysis of Online Learning Devices Development Using The PjBL-Steam Model to Improve Student Environmental Literacy - Iwan Henri Kusnadi; Ayu Anindia Hizraini; Dian Aswita; Haris Munandar; Apit Fathurohman (Departement of Mathematics Education, 2023)
Environmental literacy is a prominent 21st century learning theme that students need to master. However, data in the field shows the low environmental literacy of students in one of the schools in one city in Indonesia which is supported by several studies. Environmental literacy can be improved by applying the Project Based Learning (PjBL) model integrated with the STEAM approach. The research focuses on developing online learning tools with the PjBL-STEAM model on environmental materials to improve environmental literacy. The type of research used is Research and Development (RnD) research with the ADDIE development model which consists of analysis, design, development, implementation, and evaluation stages. The devices developed include lesson plans, LKPD, and assessment instruments. From the results of the study, valid, practical, and effective learning devices were obtained.